Sistem Informasi Penjualan Dengan Fitur Customer Relationship Management (CRM) Pada Tria Salon Berbasis Web - Welda, Welda; Sukarma, Bagus Baskara; Thalib, Emmy Febriani (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Sales is a transaction carried out by two or more parties between one person to another with a valid payment that generates an income. One of the factors of success of sales is to maintain good relationships with customers, such as giving special promotions to Pelaggan so that customers will continue to come to buy products or services offered by a company.In this study found problems such as the difficulty of determining customer loyalty, the difficulty of determining the product that must be stocked a lot, the difficulty in recording transactions because of the possibility of missing or incorrect data due to Tria salon still recording data in the ledger. In addition, other problems that arise are the delivery of promotions that take more time due to having to send the same message one by one to the customer.The solution to solving this problem is to build a sales information system with web-based customer relationship management (CRM) features. Which later can help admin performance in managing customer data, managing product and service data and managing transaction data. In addition, it can help salon owners in managing customer reports and transaction reports and can provide promotions to all customers.From the results of blackbox testing that has been done, the results obtained are that the test is in accordance with the process that is run and produces an output that is in accordance with the system functions that have been defined.